Current practice in identifying and treating cardiovascular risk, with a focus on residual risk associated with atherogenic dyslipidaemia - Ferrari, Roberto; Aguiar, Carlos; Alegria, Eduardo; Bonadonna, Riccardo C; Cosentino, Francesco; Elisaf, Moses; Farnier, Michel; Ferrières, Jean; Filardi, Pasquale Perrone; Hancu, Nicolae; Kayikcioglu, Meral; Mello E Silva, Alberto; et al. (European heart journal supplements, 2016)
A panel of European experts on lipids and cardiovascular disease discussed clinical approaches to managing cardiovascular risk in clinical practice, including residual cardiovascular risk associated with lipid abnormalities, such as atherogenic dyslipidaemia (AD). A simplified definition of AD was proposed to enhance understanding of this condition, its prevalence, and its impact on cardiovascular risk. Atherogenic dyslipidaemia can be defined by high fasting triglyceride levels (≥2.3 mmol/L) and low high-density lipoprotein cholesterol (HDL-c) levels (≤1.0 and ≤1.3 mmol/L in men and women, respectively) in statin-treated patients at high cardiovascular risk. The use of a single marker for the diagnosis and treatment of AD, such as non-HDL-c, was advocated. Interventions including lifestyle optimization and low-density lipoprotein (LDL)-lowering therapy with statins (±ezetimibe) are implemented by all experts. Treatment of residual AD can be performed with the addition of fenofibrate, since it can improve the complete lipoprotein profile and reduce the risk of cardiovascular events in patients with AD. Specific clinical scenarios in which fenofibrate may be prescribed are discussed, and include patients with very high triglycerides (≥5.6 mmol/L), patients who are intolerant or resistant to statins, and patients with AD and at high cardiovascular risk. The fenofibrate-statin combination was considered by the experts to benefit from a favourable benefit-risk profile. Cardiovascular experts adopt a multifaceted approach to the prevention of atherosclerotic cardiovascular disease, with lifestyle optimization, LDL-lowering therapy, and treatment of AD with fenofibrate routinely used to help reduce a patient's overall cardiovascular risk.
Keywords: Cardiovascular risk; Statin; Atherogenic dyslipidaemia; Residual cardiovascular risk; Fenofibrate–statin combination therapy; Fenofibrate